Molecular uropathology and cancer genetics for the urologist: key findings for classification and diagnosis. Issue 5 (18th September 2022) - Compérat, Eva; Oszwald, André; Wasinger, Gabriel; Kläger, Johannes; Hassler, Melanie R.; Shariat, Shahrokh F.
Abstract : Purpose of review: To highlight the latest changes in prostate cancer (PCa), urothelial carcinoma, upper tract urothelial carcinoma (UTUC) and renal cell carcinoma (RCC) diagnosis and the impact of genetics in this field. Recent findings: Breast cancer1/2 mutations start to play a major role in PCa treatment with regard to personalized medicine. In urothelial carcinoma an overlap between histological pathological and molecular findings exists, fibroblast growth factor receptor alteration are starting to play a major role, programmed death-ligand 1 although problematic is still important in the treatment setting. UTUC is rare, but genetically different from urothelial carcinoma. In the development of RCC, different genetic pathways such as Von Hippel–Lindau, but also tuberous sclerosis 1/2 and others play a major role in tumor development. Summary: Over the last years, genetics has become increasingly important role in the diagnosis and the treatment of patients with urological malignancies. The upcoming 5th edition (1) of the WHO still considers conventional surgical pathology as the diagnostic gold standard, but molecular pathology is gaining importance not only for diagnosis, but also in personalized treatment, of prostate, kidney cancer and urothelial carcinomas. Therefore, a close collaboration between surgical urology, pathology and oncology departments is mandatory. In this review, we will discuss the latest evolutions in PCa, urothelial carcinoma, upper urinary tract carcinomas and RCC s in the field of genetics in urology.